2006
DOI: 10.1007/s00049-006-0343-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased content of leaf surface flavonoids on the performance of mountain birch feeding sawflies vary for early and late season species

Abstract: The effects of artificially added flavonoid aglycones to birch leaf surfaces on the larval performance of six species of leaf-chewing sawflies were investigated. Significantly negative effects of increased contents of both total flavonoid and individually fed flavonoid compounds were found for the larval performance of certain mid to late and late, but not early season, sawfly species. Species-specific variations in the quantity of faecal flavonoid glycosides, which were examined to investigate whether effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…While many studies on herbivorous insects have reported clear effects on offspring performance of leaf size (Whitham 1978;Faeth 1991), phenolic content (Lane et al 1985;Beninger et al 2004;Lahtinen et al 2006), and the presence of conspecifics (Connor & Beck 1993;Roslin et al 2006), the females in our study did not seem to respond to any of these leaf attributes. The relations were either non-existent or highly complex, as with respect to leaf area.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…While many studies on herbivorous insects have reported clear effects on offspring performance of leaf size (Whitham 1978;Faeth 1991), phenolic content (Lane et al 1985;Beninger et al 2004;Lahtinen et al 2006), and the presence of conspecifics (Connor & Beck 1993;Roslin et al 2006), the females in our study did not seem to respond to any of these leaf attributes. The relations were either non-existent or highly complex, as with respect to leaf area.…”
Section: Discussioncontrasting
confidence: 85%
“…1985;Beninger et al . 2004;Lahtinen et al . 2006), or the presence of conspecifics (Denno, McClure & Ott 1995;Roslin & Roland 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The roles of primary and secondary com-pounds on aphid feeding and probing behaviour have been studied for decades. For instance, it has been reported that aphid feeding and probing behaviour can be affected by primary compounds such as sucrose (Pescod et al, 2007), and secondary compounds such as glycosides (Takemura et al, 2006), glucosinolates (Kim and Jander, 2007;Nam and Hardie, 2012) and phenolic substances (Wójcicka, 2010;Lahtinen et al, 2006). Jones et al (2002) and Rapley et al (2004) suggested that benzyl n-tetracosanoate in the epicuticular waxes of E. globulus was a biologically active component responsible for the repellence of oviposition by female M. privata.…”
Section: Discussionmentioning
confidence: 99%
“…None of the other examined defensive traits had a significant impact on leaf‐chewing insects, although their detrimental effect on certain insect species’ feeding or survival has been repeatedly recorded (Raupp, ; Zvereva et al., ; Kopper et al., ; Lahtinen et al., ). Similar situations in which recognized defensive traits, such as trichomes or latex outflow, do not affect insect population densities have been recorded before (Basset & Novotny, ).…”
Section: Discussionmentioning
confidence: 99%